PENGARUH WAKTU TUNGGU DAN PERSEPSI HARGA TERHADAP KEPUASAN DALAM MEMBENTUK LOYALITAS PELANGGAN - Gunawan, I Kadek; Oktora, I Gede Nandya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The users of four-wheeled vehicles, which are always increasing every year, indirectly need the means to repair the vehicle. This study aims to analyze the effect of waiting time, price perceptions and customer satisfaction, analyze the effect of customer satisfaction on customer loyalty, and analyze the role of customer satisfaction in mediating the effect of price perceptions and waiting time on customer loyalty at PT. Astrido Jaya Mobilindo. Respondents in this study are people who have made repairs at PT. Astrido Jaya Mobilindo. The number of research respondents was determined as many as 120 respondents. Research data obtained through research questionnaires. The analysis technique used in this study is descriptive analysis, inferential analysis. This inferential analysis uses PLS (Partial Least Square). The results of this study: 1) waiting time and price perceptions have a positive effect on customer satisfaction, 2) waiting time and price perceptions have a positive effect on customer loyalty, 3) satisfaction has a positive and significant effect on customer loyalty, 4) customer satisfaction mediates price perceptions and waiting time on customer loyalty PT. Astrido Jaya Mobilindo